(untitled) (International Journal of Physiotherapy, 2016)
Background: Asian Indians have a higher operative and overall increased mortality following coronary bypass surgery. They also have higher rates of post operative complications and repeat surgeries. Apart from physiological complications like post-operative pain, atelectasis, deep vein thrombosis, the psychological disorders are like anxiety and stress also predominantly play a major role in the morbidity of the post-surgical conditions. The aim of study is to know the influence of music therapy and breathing exercises on post-surgical cardiac diseased individuals. To evaluate the influence of music therapy and breathing exercises on physiological parameters(BP,HR,RR) in post surgical cardiac diseased individuals by using electro cardio monitor and state-trait anxiety scale. Methods: Subjects were randomly divided into two groups. Experimental group, where the subjects received music therapy and breathing exercises. Control group, where the subjects received breathing exercises. All the participants were assessed with STAI scale and physiological parameters like blood pressure, heart rate and respiration rate for both groups before and after the treatment. Paired sample t-test was used to compare the STAI scale and physiological parameters within the groups. Result: Results showed a significant improvement in both the groups but, more improvement was seen in experimental group compared to control group. Conclusion: Results suggested that music therapy and breathing exercises influences more effective than breathing exercises alone.